2009
DOI: 10.1051/0004-6361/200811099
|View full text |Cite
|
Sign up to set email alerts
|

Dense and warm molecular gas in the envelopes and outflows of southern low-mass protostars

Abstract: Context. Observations of dense molecular gas lie at the basis of our understanding of the density and temperature structure of protostellar envelopes and molecular outflows. The Atacama Pathfinder EXperiment (APEX) opens up the study of southern (Dec < −35 • ) protostars. Aims. We aim to characterize the properties of the protostellar envelope, molecular outflow and surrounding cloud, through observations of high excitation molecular lines within a sample of 16 southern sources presumed to be embedded YSOs, in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
87
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 62 publications
(101 citation statements)
references
References 87 publications
14
87
0
Order By: Relevance
“…Combined with the flux derived from the unresolved line observed with PACS, this constrains the line width to FWHM > ∼ 11 km s −1 . This width is much broader than expected for the quiescent envelope from ground-based observations (van Kempen et al 2009a) and indicates that the observed OH emission most likely stems from shocked gas in HH 46.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Combined with the flux derived from the unresolved line observed with PACS, this constrains the line width to FWHM > ∼ 11 km s −1 . This width is much broader than expected for the quiescent envelope from ground-based observations (van Kempen et al 2009a) and indicates that the observed OH emission most likely stems from shocked gas in HH 46.…”
Section: Discussionmentioning
confidence: 65%
“…For comparison, the FWHM of the H 2 O 1 10 −1 01 transition derived from recent unpublished HIFI observations is about 16 km s −1 . The CO(6−5) and CO(7−6) lines observed with APEX by van Kempen et al (2009a) are narrower. In a similar HIFI observation, OH emission was tentatively detected below the 5σ level for the strongest triplet component in NGC 1333 IRAS 2A, in agreement with the upper limits on OH emission in the PACS observation of the same source.…”
Section: Discussionmentioning
confidence: 85%
“…Even though the position where van Kempen et al (2009) observed the C 18 O (3-2) and the HCO + (4-3) lines, the YSO, lies between the mapping positions in this paper, their measurement can be used to evaluate the nature of the C 18 O_maximum. The APEX beam size at 319 GHz is similar to the SEST beam size at 220 GHz, which makes comparing the line intensities observed with APEX and SEST realistic.…”
Section: O Mappingmentioning
confidence: 79%
“…Even though the emission from high density tracers is weak in the CG 12 C 18 O hotspot, the C 18 O (3-2) T MB of 10 K is high compared to the T MB temperatures in the (2-1) and (1-0) transitions (5 K and 2.2 K, respectively). Observations of the high density tracers (van Kempen et al 2009) and C 18 O thus indicate that C 18 O_maximum is a moderately dense elongated structure west of the YSO position.…”
Section: O Mappingmentioning
confidence: 89%
See 1 more Smart Citation